Правове забезпечення корпоративних правовідносин: пріоритет за імперативністю чи диспозитивністю - Жорнокуй, Ю. М.; Zhornokui, Yu. M.; Жорнокуй Юрій Михайлович (Право і безпека. – 2023. – № 1 (88). – С. 113-122, 2023)
Проаналізовано сучасний стан правового забезпечення корпоративних відносин і доктринальних підходів щодо визначення пріоритетності за їх імперативним чи диспозитивним регулюванням. На сучасному етапі розвитку корпоративного законодавства маємо поєднання диспозитивних та імперативних механізмів нормативного забезпечення корпоративних відносин. Досліджувана система нормативних актів не дозволяє однозначно відповісти на питання про пріоритетність застосування щодо цих відносин диспозитивного чи імперативного методу. Незважаючи на те, що корпоративні відносини як цивільні підпорядковані загальним засадам цивільного законодавства, необхідність забезпечення стабільності цивільного обороту та захисту прав їх учасників зумовлює потребу в імперативному врегулюванні окремих аспектів корпоративного руху. Окреслено тенденцію розширення сфери диспозитивних засад у механізмі правового регулювання корпоративних відносин за рахунок конструкції корпоративного договору.

Current state of legal support for corporate relations and doctrinal approaches to determining the priority of their mandatory or dispositive regulation have been analyzed. Attention has been drawn to the fact that in order to ensure unimpeded exercise of subjective corporate rights by each participant of a corporate organisation, a balance of regulatory regulation and self-regulation should be developed, which should be built from mandatory requirements to discretionary principles. At the current stage of the corporate legislation development, there is a combination of dispositive and mandatory mechanisms of regulatory support of corporate legal relations. The regulatory framework for the establishment, operation and termination of corporations, as well as the exercise and protection of the rights of their participants (shareholders), does not allow a clear answer to the question of the priority of applying the dispositive or mandatory method to these relations. Despite the fact that corporate relations being civil are subject to the general principles of civil law, the need to ensure the stability of civil turnover and protect the rights of their participants necessitates the urgent regulation of certain aspects of corporate movement. It has been identified a tendency to expand the scope of dispositive principles in the mechanism of legal regulation of corporate relations. It is clearly crystallised in relation to certain organisational and legal forms of corporate entities. For objective reasons, it is less evident in relation to a public joint-stock company. The development of self-regulatory elements in relation to a limited liability company could be welcomed, given its intermediate position between the classic business entity such as a joint-stock company and a general or limited partnership. However, with regard to a private joint-stock company, the possibility of strengthening the dispositive principles should be taken with caution. Despite its non-public nature, such a company remains, first and foremost, a capital association and should not be transformed into a limited liability company, and its shares should not be recognised as a surrogate for securities. Although the corporate agreement contains provisions on the exercise (refusal to exercise) of corporate rights by participants (shareholders), they are not local, but are individual regulators that do not apply to the scope of the company's functioning and activities, which does not indicate the normative nature of such a contractual structure.

Проанализировано современное состояние правового обеспечения корпоративных отношений и доктринальных подходов в отношении определения приоритетности за их императивным или диспозитивным регулированием. На современном этапе развития корпоративного законодательства имеем объединение диспозитивных и императивных механизмов нормативного обеспечения корпоративных отношений. Исследуемая система нормативных актов не дает возможности однозначно ответить на вопрос о приоритетности применения к этим отношениям диспозитивного или императивного метода. Невзирая на то, что корпоративные отношения как гражданские подчинены общим основам гражданского законодательства, необходимость обеспечения стабильности гражданского оборота и защиты прав их участников обуславливает императивное урегулирование отдельных аспектов корпоративного движения. Очерчивается тенденция расширения сферы диспозитивных начал в механизме правового регулирования корпоративных отношений за счет конструкции корпоративного договора.
Legal support of corporate legal relations: priority in terms of imperative or discretionary nature
Правовое обеспечение корпоративных правоотношений: приоритет за императивностью или диспозитивностью
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; корпоративні відносини; corporate relations; корпоративные отношения; правове забезпечення; legal support; правовое обеспечение; корпоративний договір; corporate agreement; корпоративный договор; диспозитивність; dispositivity; диспозитивность; імперативність; imperativeness; императивность